EFEKTIVITAS PESAN DAKWAH MELALUI KHUTBAH JUM??AT DI MASJID JAMI BAITUL MUSLIMIN DESA SROBYONG JEPARA - Noor Rohman Fauzan; Ahmad Nurisman (An-Nida : Jurnal Komunikasi Islam, 2014)
Abstract Keywords Missionary activity is successful or effective when the message delivered by the preacher to the subject of propaganda (mad??u) can be understood as a whole and expressed in action. A preacher let understand the character mad??u, knowing classification and character mad??u propaganda messages to be well received. The research objective was to determine the effectiveness of propa- ganda message conveyed through the media Friday sermon to influence or shape the behavior of religious citizens living around the Baitul Muslim Jami Srobyong Village. The method used is a combination of research methods (mixed method) between qualitative and quantitative research. Data obtained by distributing questionnaires to 50 respondents randomly question citizens about Jami Baitul Muslims, as well as interviews with the preacher. The re- sults of the effectiveness of propaganda messages through Friday sermon in the form of religious behavior the result of 70% answered effectively, seriousness mad??u in listening to the sermon obtained results of 74%. The increase in terms of religious and charitable sunnah prayers obtained results 68% and 72%